1992
DOI: 10.1063/1.108147
|View full text |Cite
|
Sign up to set email alerts
|

Visible photoluminescence of silicon-based nanostructures: Porous silicon and small silicon-based clusters

Abstract: We have studied and compared the optical properties of both porous Si and the chemically synthesized planar and cubic Si skeleton clusters. Broad photoluminescence with large Stokes shifts were observed at the visible region in both samples. Spectroscopic analysis suggests that the surface of porous Si is similar to a condensation of Si clusters. Small Si clusters play a key role in the strong room-temperature photoluminescence in porous Si.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…The results presented here are in general agreement with experimental [13] and theoretical [14] observations of optical spectra for chains of silicon atoms. It has been found that light absorption on chains consisting of small number of Si atoms (n ≤ 20) occurs at higher energies than in longer structures.…”
Section: Calculated Electronic and Optical Propertiessupporting
confidence: 80%
See 1 more Smart Citation
“…The results presented here are in general agreement with experimental [13] and theoretical [14] observations of optical spectra for chains of silicon atoms. It has been found that light absorption on chains consisting of small number of Si atoms (n ≤ 20) occurs at higher energies than in longer structures.…”
Section: Calculated Electronic and Optical Propertiessupporting
confidence: 80%
“…It has been found that light absorption on chains consisting of small number of Si atoms (n ≤ 20) occurs at higher energies than in longer structures. When the number of atoms in the chains increases, the energy absorption tends to a constant value (n ≥ 80) [13]. Here, we find the same qualitative behavior in 2 .…”
Section: Calculated Electronic and Optical Propertiessupporting
confidence: 72%
“…26 Figure 3 shows the square root of the PLE intensity versus the excitation energy for the closepacked SiC nanocrystal film. 26 Figure 3 shows the square root of the PLE intensity versus the excitation energy for the closepacked SiC nanocrystal film.…”
mentioning
confidence: 99%
“…Because the local Si structures can be controlled in chemically synthesized Si polymers, studies of optical properties of Si polymers with different backbone structures help to understand the electronic structures and the microscopic PL mechanisms in a variety of Si-based materials. Moreover, studies of optical properties of small Si clusters help to understand the dimension effects on electronic properties of Si-based nanostructure, and the mechanism of visible PL in nanometer-size Si crystallites such as porous Si (5).…”
mentioning
confidence: 99%